The effect of kenaf filler reinforcement on the mechanical and physical properties of injection moulded polypropylene composites - Mohd Khairul Fadzly Md Radzi,; Norhamidi Muhamad,; Akhtar, Majid Niaz; Zakaria Razak,; Farhana Mohd Foudzi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Natural fibres potentially offer better reinforcement to improve the mechanical and physical properties of polymer composites. However, these natural materials at this stage are not fully explored yet due to the fibres themselves have limited heat resistance and are quite sensitive to moisture. This limitation will weaken the adhesion when interacting with thermoplastic matrices during the processing of composites. Therefore, the main purpose of this study is to investigate inherent strength characteristics among kenaf (core and bast) fillers as a reinforcement in polypropylene composites at various geometries and loadings via the injection moulding process. The composite materials consisted of kenaf with the geometric core filler of the 20 mesh (992 μm), 40 mesh (460 μm) and bast filler (166.9 μm) were mixed with polypropylene based on the filler loadings of 10 up to 40 wt. %. The results showed that bast filled composites had the highest tensile strength of 19.52 MPa at 30 wt. %, compared to core filled composites. Instead, 20 mesh core filled composites were obtained had the highest flexural strength which values were 25 MPa and 29 MPa at 20 wt. % and 30 wt. %, respectively. While 40 mesh core filled composites had the highest values of 25.35 MPa at 40 wt. % of filler loading compared to bast filled composites. SEM micrograph images showed the good interfacial bonding of core filler which surrounded by PP leading to diffusion and permeation of bonding. In conclusion, the use of kenaf (core and bast) fillers as a reinforcement in composite materials is reasonable to maximise the use of fibre from natural sources.